2003
DOI: 10.1192/bjp.182.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and delusional ideation

Abstract: Perceived discrimination may induce delusional ideation and thus contribute to the high observed rates of psychotic disorder in exposed minority populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
203
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(220 citation statements)
references
References 24 publications
11
203
2
4
Order By: Relevance
“…Third, would trauma-related variables be positively associated with psychotic experiences and substance related variables? Fourth, when traumatic experiences and illegal substance use are considered simultaneously, would both jointly be positively associated with psychotic experiences, controlling for potential confounders (age, origin, socioeconomic status) known from the literature (Janssen et al, 2003;Janssen et al, 2004;Veling et al, 2007). Last, because juvenile detainees are expected to show high levels of paranoia-related experiences that may be related to their history and current legal status, for example because they are secretly being watched during detention (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Third, would trauma-related variables be positively associated with psychotic experiences and substance related variables? Fourth, when traumatic experiences and illegal substance use are considered simultaneously, would both jointly be positively associated with psychotic experiences, controlling for potential confounders (age, origin, socioeconomic status) known from the literature (Janssen et al, 2003;Janssen et al, 2004;Veling et al, 2007). Last, because juvenile detainees are expected to show high levels of paranoia-related experiences that may be related to their history and current legal status, for example because they are secretly being watched during detention (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…27 Perceived discrimination has been found to be associated with more severe positive symptoms, as well as more severe symptoms of depression and anxiety, among migrants with a psychotic disorder. 28 Similarly, experiences of discrimination have been found to be associated with psychotic experi ences, 29 delusional ideation 30 and attenuated positive psychotic symptoms. 31 Canadian research suggests that experiences of discrimination contribute to declines in mental health status among migrants, 32 although data are lacking on their contribution to psychosis specifically.…”
Section: Role Of Visible Minority Statusmentioning
confidence: 99%
“…Individuals with darker skin colour, irrespective of social class, experience higher levels of discrimination than do other ethnic groups (Williams & Williams-Morris, 2000). Interestingly, in a recent prospective study, previously healthy individuals who reported discrimination were at an increased risk of developing psychotic symptoms (Janssen et al 2003). Discrimination may lead to stress, low self-esteem, and increased use of psychoactive substances (Krieger, 2000), factors that are themselves currently implicated in the development of schizophrenia (Selten & Cantor-Graae, 2004).…”
Section: Introductionmentioning
confidence: 99%